The Selfish Giant - Wilde, Oscar (Italy ELI - Young Readers, 2016)
When a great Giant returns home to his castle, he discovers that the local children have been playing in his magnificent garden and decides to build a high stone wall around the garden to keep them out. Suddenly the birds no longer visit and the flowers die, Miss Winter spreads her white blanket of snow over the lush green grass. Everyone is sad and unhappy. Find out how the Giant makes amends and the yard, once more, becomes a glorious garden
Picture dictionary, games and activities.
Keywords: Story; Language Learning; Classroom activities; Beginner/Elementary level